Discovering stable genomic regions linked to powdery mildew adult-plant resistance in wheat - Mourad, Amira M. I.; Sallam, Ahmed; Börner, Andreas; Hamdy, Rania M.; Esmail, Samar M. (Frontiers in Agronomy, 2025)
Wheat powdery mildew (WPM) is a devastating disease that causes significant yield losses worldwide. In Egypt, a lake in immune cultivars was reported and little is known about its genetic control. In this study, two different plant sets (the isoline set and the test set) were evaluated for WPM adult plant resistance (APR-WPM) over three cropping seasons (2021-2022, 2022-2023, and 2023-2024). The results of the isoline set revealed that the Pm1b, Pm34, Pm36, MIAG12, and NACG13 resistance genes were stable among the three cropping seasons. The results of the evaluated set revealed highly significant differences among the cropping seasons as well as among the tested genotypes, suggesting the presence of different Blumeria graminis f. sp. tritici (Bgt) races and the potential to select highly resistant genotypes. Eight resistant genotypes belonging to five different countries, excluding Egypt, were identified. A genome-wide association study (GWAS) was performed using each cropping season separately as well as the average of the three seasons. GWAS was done using two different SNP data sets, GBS and 25K-SNP array. A total of 86 significant markers associated with resistance were identified. Among these markers, only four markers were stable across at least two seasons. Three gene models harboring these markers were detected and functionally annotated to be linked with disease resistance. Gene enrichment analysis revealed that each gene model regulated a single network of different biological processes and molecular function pathways. Among the resistant genotypes, one Sudanese genotype was selected for its strong WPM resistance and high yield potential. This genotype was also found to be highly adapted to the Egyptian environment and a high-yielding genotype. The incorporation of this genotype into future breeding programs could increase the resilience of Egyptian wheat germplasm.